The sky as a lived space: Perceptions of the celestial space in everyday life in Curitiba, Brazil - Duarte Dalmolin, Adriano; Torres, Marcos Alberto (Aprender, 2025)
Researching the sky through a cultural-geographic approach can reveal the relationship between the symbolic universe present in the sky and everyday practices across different cultures. Studying the perception of celestial space as lived space is possible through a phenomenological approach, as it enables understanding how people relate to the sky, exploring it as part of their daily lives and a way to comprehend their own existence. However, in urban centers, this connection has been weakened by “sky erasure” due to light and pollution, while among traditional populations, the erasure is political, as hegemonic culture disregards their ancestral knowledge. This work aims to deepen the understanding of the sky’s influence on social relations based on individuals’ perceptions of the celestial space over Curitiba (Brazil). By framing the sky as a geographic space, it becomes possible to reclaim this connection in a world marked by haste. The methodology employed in this study sought to evoke the “sense of place” of the sky through photographs taken by nine individuals, focusing on daily life, territorialities, and the features of the sky in the urban landscape. By capturing the sky and reflecting on their daily experiences, people tend to develop a bond with it, restoring lost connections caused by urban expansion.
Keywords: Sky; Celestial Space; Perception; Everyday life